Enhancement of methane production from long chain fatty acid based effluents - Cavaleiro, A. J. (2008)
Two anaerobic sludges previously loaded with oleate and palmitate accumulated 4570 ± 257 and 5200 ± 9 mgCOD-LCFA gVSS−1, respectively. These sludges were incubated in batch assays and methane production was recorded after addition of 100–900 mg L−1 of oleate and palmitate, respectively. The batch assays were conducted before and after allowing the depletion of the biomass-associated LCFA. The presence of biomass-associated LCFA decreased the capacity of both sludges to convert the added LCFA to methane. After the degradation of biomass-associated LCFA, the lag phases observed before the onset of methane production were significantly reduced, evidencing an increase in the tolerance of the acetotrophic methanogens to the presence of LCFA. In another experiment, three recurrent pulses were performed with a real dairy wastewater containing 3.6 gCOD L−1, from which 53% was fat. Methane yields of 0.45 ± 0.01, 0.88 ± 0.02 and 1.29 ± 0.08 gCOD- CH4 gCODfed-1 were achieved in the first, second and third pulses, respectively, evidencing an increasing capacity of the sludge to convert substrate accumulated in previous additions.